Studi Deskriptif Pengetahuan Wanita Usia Subur Tentang Penggunaan Kontrasepsi Alat Kontrasepsi Dalam Lahir (AKDR) - Intan Sari; Yuhemy Zurizah (STIKes Budi Mulia Sriwijaya, 2024)
The very fast rate of population growth encourages the government to continue to suppress the rate of population increase through the Family Planning (KB) program by increasing family planning participants. This arises and occurs due to low understanding and understanding and responsibility regarding the function of Protection and Family Planning (KB) tools. Apart from that, the Family Planning (KB) program also has an important role in reducing the Maternal Mortality Rate (MMR). The aim of this research was to determine WUS' knowledge regarding the IUD contraceptive device at the Budi Mulia Medika Palembang Maternity Clinic, as well as to determine the characteristics of WUS including age, education and occupation. This research used a descriptive method with a population of 3624 people and a sample of 362 respondents who met the inclusion criteria. The instrument used was a questionnaire. Validity test using the SPSS program and reliability using the Cronbach's Alpha formula. Most of the respondents' age was >30 years as many as 216 people (59.67%), most of the respondents' education was primary education as many as 163 people (45.03%) and most of the respondents were working as many as 283 people (78.18%). WUS knowledge about IUDs at the Budi Mulia Medika Palembang Maternity Clinic was mostly lacking, namely 149 people (41.16%). Based on the research results obtained, it is hoped that there will be participation from various parties in providing information and health education regarding the IUD contraceptive device. Apart from that, there is a need for further intervention regarding knowledge material about the IUD contraceptive device which is not yet fully known by, especially the Women of Childbearing Age (WUS) community